Assistance for people with disabilities: The performance of nurses in Primary Health Care (Research, Society and Development, 2021)
This study aimed to understand the role of nurses in Primary Health Care in assisting people with disabilities. This is a descriptive study with a qualitative approach, carried out with nurses from five Family Health Units in a municipality in the interior of Bahia, where supervised internship practices at the State University of Bahia, Campus XII took place. Data collection was carried out through electronic questionnaires sent by e-mail to professionals, after electronic signature of the Free and Informed Consent Term. Questions were made regarding the object of the study. For data analysis, the Thematic Content Analysis technique described by Bardin was used. The research respected the ethical and scientific aspects in accordance with Resolution No. 466 of 2012 of the National Health Council. After analyzing the material, the following categories emerged: Health care practices for people with disabilities in Primary Health Care; Difficulties encountered by Primary Health Care nurses in assisting people with disabilities. The role of nurses in assisting People with Disabilities in Primary Health Care is permeated by numerous challenges and difficulties, such as the lack of adequate structure, difficulty in communication and training to meet the needs of this group. In addition to these, it notes structural governmental weaknesses in the implementation of policies that already exist to guarantee the rights of people with disabilities.